Faktor yang mempengaruhi niat menggunakan teknologi Balanced Scorecard (BSC) oleh para level manajer sektor kesehatan di Indonesia - Fitri Emi Sri Parastri (Health Sciences and Pharmacy Journal, 2019)
The health care industry is a capital-intensive, labor-intensive, and full information, with performance information that requires high concentration and attention from the health manager. Balanced Scorecard (BSC) is an importance technological innovation as a performance measurement system that strategically and allow manager translate organizational strategies into the mission and performance indicators with reality acceptance and its own variation response among users. The aim of this study is to determine the factor of affecting hospital managers’ behavior intention in implementing the balanced scorecard. This research type was quantitative with cross sectional design. The sampling technique using purposive sampling. The samples were 60 respondents. The data collected by questionnaires analyzed with multiple linear regression test. The quantitative analysis’ results of 60 samples showed that a simultaneous influence of easy perceive of using and usefulness perceive on behavioral intention in implementing BSC (Sig = 0,000 0,05) and easy perceive of using have influence on perceive of usefulness (Sig = 0,000 0,05). While partially easy perceive of using and usefulness perceive was affected toward behavioral intention is about (Sig = 0,422 0,05) and (Sig = 0,001 0,05), on the other side, the easy perceive of using have influence toward usefulness perceive (Sig = 0,000 0,05). The conclution was the hospital manajer's perception of the easy of use of BSC and the use of the manajer together have a significant impact on the manajer's behavioral intention to implement the BSC. The hospital manajer's perception of easy of use of the BSC had no significant effect on the intention to implement the BSC.